A Data Transmission Technique for Personal Health Systems. (10th November 2013) - Tu, Jih-Fu; Chen, Chih-yung
Abstract : We used the modular technique to design a personal health data transmitter (PHDT) that is composed of the following components: (1) the core is an embedded signal chip, (2) three kinds of transmutation modules such as USB, RF, and UART, (3) an I 2 C interface is used to acquire the users data, and (4) through Internet it links to the cloud server to store the personal-health data. By the experiment, we find that the modular manner is feasible, stable of functional, integral, and accurate, while it is exploited to design the PHDT. For the experiment, we present each module algorithm to find that our system is very helpful to people.